Usability of graphical visualizations on a tool-mounted interface for spine surgery - Schuetz, Laura; Brendle, Caroline; Esteban, Javier; Krieg, Sandro M.; Eck, Ulrich; Navab, Nassir (Journal of Imaging, 2021)
Screw placement in the correct angular trajectory is one of the most intricate tasks during spinal fusion surgery. Due to the crucial role of pedicle screw placement for the outcome of the operation, spinal navigation has been introduced into the clinical routine. Despite its positive effects on the precision and safety of the surgical procedure, local separation of the navigation information and the surgical site, combined with intricate visualizations, limit the benefits of the navigation systems. Instead of a tech-driven design, a focus on usability is required in new research approaches to enable advanced and effective visualizations. This work presents a new tool-mounted interface (TMI) for pedicle screw placement. By fixing a TMI onto the surgical instrument, physical de-coupling of the anatomical target and navigation information is resolved. A total of 18 surgeons participated in a usability study comparing the TMI to the state-of-the-art visualization on an external screen. With the usage of the TMI, significant improvements in system usability (Kruskal–Wallis test p < 0.05) were achieved. A significant reduction in mental demand and overall cognitive load, measured using a NASA-TLX (p < 0.05), were observed. Moreover, a general improvement in performance was shown by means of the surgical task time (one-way ANOVA p < 0.001).
CRIS-Team Scopus Importer:2023-03-08
Keywords: Medical augmented reality; Pedicle screw placement; Spine surgery; Surgical navigation; Tool-mounted interface; Usability; Visualization